Post-Arab Spring Narratives A Minor Literature in the Making - Younas, Abida (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book looks at eight post Arab Spring novels in the context of Gilles Deleuze's and Félix Guattari's theory of minor literature. Ahdaf Soueif, Hisham Matar, Karim Alrawi, Youssef Rakha, Yasmine El Rashidi, Omar Rober Hamilton, Saleem Haddad, and Nada Awar Jarrar all focus on the Arab world in their work; on the lives of ordinary and minority peoples; and on the revolutions of their respective nations. This volume shows how these contemporary Anglo-Arab novelists exhibit linguistic experimentation akin to Deleuze's and Guattari's theory of 'deterritorialization', but in a way that is unique to Anglo-Arab writing. The selected novelists repudiate the use of metamorphosis, which is usually an essential part of the deterritorialization of a major language. Instead, their writings enact the minor practice of linguistic deterritorialization by using metaphor and by incorporating contemporary modes of protest like popular slogans, tweets, and chants. These authors challenge theconventions of minor literature and, by adopting this mode of deterritorialization, foreground the experiences of officially silenced voices. Abida Younas is a postgraduate tutor at the University of Glasgow, UK. She has contributed to a number of journals, including "Magical Realism and Metafiction in Post-Arab Spring Literature: Narratives of Discontent or Celebration?" for the British Journal of Middle Eastern Studies (2018).
Chapter 1: Writing the Present to Commemorate: Personal Narratives of the Arab Revolution -- Chapter 2: Magical Realism and Metafiction: Rethinking Minor Literature -- Chapter 3: Post-Arab Spring Cairo: Urban Narratives as Minor Literature,- Chapter 4: The Humanitarian Narrative of the Arab-Spring: Further Towards Minor Literature .
Keywords: Middle Eastern literature; Narration (Rhetoric).; Postmodernism; Middle Eastern Literature; Narratology; Post-Modern Philosophy